Impact of occupational stress on irritable bowel syndrome pathophysiology and potential management in active duty noncombat Greek military personnel: a multicenter prospective survey. Issue 8 (August 2019) - Papaefthymiou, Apostolis; Doulberis, Michael; Kountouras, Jannis; Kolokytha, Christina; Galanopoulos, Michail; Liatsos, Christos; Kyriakos, Nikolaos; Giakoumis, Marios; Papadomichelakis, Michail; Polyzos, Stergios A.; Kotronis, Georgios; Katsinelos, Panagiotis
Abstract : Introduction: Irritable bowel syndrome (IBS) is one of the gut–brain axis interaction disorders. It has global distribution with varying prevalence and particular financial and psychological consequences. IBS has been associated with stress and anxiety, conditions that are usually prevalent in the army. There are scarce data investigating the impact of IBS on noncombat active duty military without reports of Greek military or stress in the occupational environment. Materials and methods: The main exclusion criteria in our noncombat military multicenter prospective survey were gastrointestinal pathologies, malignancies, hematochezia, recent infections and antibiotics prescription, and pregnancy. Questionnaires included a synthesis of baseline information, lifestyle, and diet, psychological and stress-investigating scales and the IBS diagnosis checklist. Hospital Anxiety and Depression Scale and Rome IV criteria were utilized. Results: Among 1605 participants included finally, the prevalence of IBS was 8% and 131 cases were identified. Women were more vulnerable to IBS, although male sex was prevalent at a ratio of 3.5 : 1 (male:female) in the entire sample. The mean age of all participants was 23.85 years; most of the IBS patients were older than thirty. Abnormal anxiety scores and high levels of occupational stress were related to an IBS diagnosis. Discussion: This prospective multicenter survey showed, for the first time, the potential impact of occupational stress on IBS in active duty noncombat Greek Military personnel. The diagnosis of IBS by questionnaire is a quick, affordable way that can upgrade, by its management, the quality of life and relieve from the military burden. Our results are comparable with previous studies, although large-scale epidemiological studies are required for the confirmation of a possible causative relationship. Abstract : Supplemental Digital Content is available in the text.